Caribbean facing up to the Twenty-First Century - Carrington, Edwin W. (CCS GeorgetownGY, 1996)
Focuses on the challenges the 21st century will bring to society as well as on the major world transformations, out of which significant opportunities could arise. Looks at the Caribbean situation in order to show how ready we are in the Region to exploit these opportunities. Suggests a ten point agenda which is needed for further Caribbean development, especially in the 21st century.